Identifying the safe operating space for food systems - te Wierik, Sofie; Declerck, Fabrice; Beusen, Arthur; Gerten, Dieter; Maggi, Federico; Norberg, Anna; Noone, Kevin; Schulte-Uebbing, Lena; Springmann, Marco; Tang, Fiona H. M.; de Vries, Wim; van Vuuren, Detlef; et al. (NATURE PORTFOLIO, 2025)
Global environmental pressures from food systems threaten biodiversity and the stability of the Earth system, yet the safe operating space for food systems is unknown. Here we calculate food system boundaries as shares of planetary boundaries, proposing budgets for the food system across nine boundaries. Our results indicate that food systems are a critical driver of planetary boundary transgressions, dominating at least four transgressed boundaries (that is, biosphere integrity, land system change, freshwater change and biogeochemical flows) while strongly contributing to the transgression of two more (that is, climate change and novel entities). Moreover, global food systems are currently beyond all nine food system boundaries; moving to the safe operating space requires reducing related greenhouse gas emissions substantially, halting the conversion of intact nature to agriculture, redistributing fertilizer inputs, limiting pesticide and antibiotic use, and preserving critical freshwater flows without negatively affecting yields.